Kernel density estimation of tensile strength and process capacity index calculation of fabric core conveyor belt - GU Qi-chun1, HE Wen-hui1, WANG Xiang1, ZHUANG Bing-jian2, ZHANG Jie2 (Hecheng xiangjiao gongye)
EP 200 fabric core conveyor belt as the research object, firstly the sample data of stress and strain were obtained through tensile strength test, secondly the data distribution was preliminary tested using QQ chart, and then the kernel density fitting probability distribution was used to verify the K-S fitting degree and correctness of the data, and finally the process capacity index of the fabric core conveyor belt was calculated. The results showed that the tensile strength distribution of the fabric core conveyor belt roughly followed a normal distribution, the kernel density estimation method could effectively solve the problem of insufficient sample data and had certain advantages in engineering, and the process capacity index could not match the yield rate of the product. Further analysis of the factors affecting the stability of full- thickness tensile strength would be beneficial for optimizing the production of conveyor belts.